2010
DOI: 10.1002/eji.200940203
|View full text |Cite
|
Sign up to set email alerts
|

DEAD/H BOX 3 (DDX3) helicase binds the RIG‐I adaptor IPS‐1 to up‐regulate IFN‐β‐inducing potential

Abstract: Retinoic acid-inducible gene-I (RIG-I)-like receptors (RLR) are members of the DEAD box helicases, and recognize viral RNA in the cytoplasm, leading to IFN-b induction through the adaptor IFN-b promoter stimulator-1 (IPS-1) (also known as Cardif, mitochondrial antiviral signaling protein or virus-induced signaling adaptor). Since uninfected cells usually harbor a trace of RIG-I, other RNA-binding proteins may participate in assembling viral RNA into the IPS-1 pathway during the initial response to infection. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
178
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 190 publications
(188 citation statements)
references
References 29 publications
8
178
2
Order By: Relevance
“…The findings in this issue that DDX3 has a positive role in IFN induction [3] are consistent with two previous reports. Schroder et al [7] showed that the vaccinia virus protein K7 inhibited PRRinduced IFN-b promoter induction by binding to DDX3, which led to the discovery that DDX3 had a positive role in the RLR pathway.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…The findings in this issue that DDX3 has a positive role in IFN induction [3] are consistent with two previous reports. Schroder et al [7] showed that the vaccinia virus protein K7 inhibited PRRinduced IFN-b promoter induction by binding to DDX3, which led to the discovery that DDX3 had a positive role in the RLR pathway.…”
supporting
confidence: 93%
“…In contrast, the role for DDX3 in RLR signalling identified in this issue by Oshiumi et al [3] seems somewhat distinct from these previous studies. Here, DDX3 is identified as an IPS-1-interacting protein via yeast-2-hybrid.…”
contrasting
confidence: 87%
See 3 more Smart Citations